EFFECT of daily antiseptic body wash with octenidine on nosocomial primary bacteraemia and nosocomial multidrug-resistant organisms in intensive care units: design of a multicentre, cluster-randomised, double-blind, cross-over study. Issue 11 (8th November 2017) - Meißner, Anne; Hasenclever, Dirk; Brosteanu, Oana; Chaberny, Iris Freya
Abstract : Introduction: Nosocomial infections are serious complications that increase morbidity, mortality and costs and could potentially be avoidable. Antiseptic body wash is an approach to reduce dermal micro-organisms as potential pathogens on the skin. Large-scale trials with chlorhexidine as the antiseptic agent suggest a reduction of nosocomial infection rates. Octenidine is a promising alternative agent which could be more effective against Gram-negative organisms. We hypothesise that daily antiseptic body wash with octenidine reduces the risk of intensive care unit (ICU)-acquired primary bacteraemia and ICU-acquired multidrug-resistant organisms (MDRO) in a standard care setting. Methods and analysis: EFFECT is a controlled, cluster-randomised, double-blind study. The experimental intervention consists in using octenidine-impregnated wash mitts for the daily routine washing procedure of the patients. This will be compared with using placebo wash mitts. Replacing existing washing methods is the only interference into clinical routine. Participating ICUs are randomised in an AB/BA cross-over design. There are two 15-month periods, each consisting of a 3-month wash-out period followed by a 12-month intervention and observation period. Randomisation determines only the sequence in which octenidine-impregnated or placebo wash mitts are used. ICUs are left unaware of what mitts packages they are using. The two coprimary endpoints are ICU-acquired primary bacteraemia and ICU-acquired MDRO. Endpoints are defined based on individual ward-movement history and microbiological test results taken from the hospital information systems without need for extra documentation. Data on clinical symptoms of infection are not collected. EFFECT aims at recruiting about 45 ICUs with about 225 000 patient-days per year. Ethics and dissemination: The study was approved by the ethics committee of the University of Leipzig (number 340/16-ek) in November 2016. Findings will be published in peer-reviewed journals. Trial registration number: DRKS-ID: DRKS00011282.